Stepwise Methanolysis of Waste Cooking Oil Using Immobilized Thermomyces lanuginose Lipase within Ultrasonic-assisted Condition - Nur Sabrina Abdul Manab; Harumi Veny; Azziana Gusniah; Sarina Sulaiman; Noorhaliza Aziz (ASEAN Journal of Chemical Engineering, 2021)
Biodiesel or fatty acid methyl ester is a fuel derived from vegetable oil and animal fat. In this study, biodiesel is produced from transesterification of waste cooking oil and methanol (methanolysis), using immobilized Thermomyces lanuginose (TLIM) within ultrasonic-assisted conditions. The enzymatic transesterification is used due to environmental concerns and also the high yield of biodiesel. The limitations in the mass transfer rate of the product and longer reaction time have drawn attention to more efficient technology. One of them is ultrasonic-assisted to reduce reaction time and increase the catalytic activity of the enzyme. Various parameters have been examined in this study, such as reaction time, methanol to oil ratio, the effect of temperatures, and temperature dependency of immobilized Thermomyces lanuginose (TLIM). The highest biodiesel yield of 69.3% was obtained after 6 hours of reaction at a temperature of 35°C and using three step-wise addition of methanol to oil ratio 3:1. Our study showed that the TLIM is sensitive to methanol to oil molar ratio above 1:1. Further research on the temperature dependence found that the TLIM activation energy in the reaction is 11.9 kcal/mol, which is within activation energy for an enzymatic reaction.